2015
DOI: 10.1021/acs.biochem.5b00875
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Dynamic Changes Accompany Hck Activation by HIV-1 Nef and are Reversed by an Antiretroviral Kinase Inhibitor

Abstract: The HIV-1 virulence factor Nef interacts with the macrophage Src-family kinase Hck, resulting in constitutive kinase activation that contributes to viral replication and immune escape. Previous chemical library screens identified the diphenylfuranopyrimdine kinase inhibitor DFP-4AB, which selectively inhibits Nef-dependent Hck activity in biochemical assays and potently blocks HIV replication in vitro. In the present study, hydrogen exchange mass spectrometry (HX MS) was used to study conformational changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…To test this possibility, HX MS was used to compare the rates of deuterium uptake by the Fgr and Src SH3-SH2 dual domains alone and in the context of near-full-length kinases that also include the linker, kinase domain, and phosphorylated tail. The SH3 and SH2 domains of both Fgr and Src were protected from deuterium uptake in the context of the near-full-length kinases, as reported previously for inactive Hck (40). This result suggests that the Fgr core region adopts an assembled conformation similar to inactive Src and Hck, although these intramolecular contacts do not appear to regulate Fgr kinase domain activity.…”
Section: Discussionsupporting
confidence: 77%
“…To test this possibility, HX MS was used to compare the rates of deuterium uptake by the Fgr and Src SH3-SH2 dual domains alone and in the context of near-full-length kinases that also include the linker, kinase domain, and phosphorylated tail. The SH3 and SH2 domains of both Fgr and Src were protected from deuterium uptake in the context of the near-full-length kinases, as reported previously for inactive Hck (40). This result suggests that the Fgr core region adopts an assembled conformation similar to inactive Src and Hck, although these intramolecular contacts do not appear to regulate Fgr kinase domain activity.…”
Section: Discussionsupporting
confidence: 77%
“…While these compounds work directly via the Hck active site, they showed enhanced potency for Hck inhibition in the presence of Nef, suggesting that Nef binding may allosterically impact the Hck active site to enhance inhibitor binding. This conclusion is supported by subsequent HX MS studies of the Nef•Hck complex in the presence of a DFP-based compound with antiretroviral activity (74). DFP-based Hck inhibitors also blocked Nef-mediated enhancement of viral replication across a wide range of Nef subtypes, providing additional evidence that Src-family kinase signaling is important to viral replication (101).…”
Section: Harnessing Kinase Activation By Nef For Anti-retroviral Drugmentioning
confidence: 81%
“…HX MS is particularly powerful when used to compare two states of a given protein -for example, Hck in the presence and absence of Nef. Wales et al performed this comparison using recombinant near-full-length Hck (SH3-SH2-kinase-tail) and full-length Nef (74). The crystal structure of the identical near-full-length Hck protein has been reported (75) and shows that it adopts an assembled, inactive conformation driven by two primary intramolecular interactions: the SH3 domain binds to the SH2-kinase linker (which adopts a PPII helical conformation) while the SH2 domain engages the tyrosine-phosphorylated tail.…”
Section: Structural Basis Of Src-family Kinase Activation Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Both hypotheses are consistent with increased linker accessibility and faster thermolysin cleavage rate. The latter hypothesis is supported by Smithgall and Engen who have shown that activation of Hck (a Src family kinase) by HIV-1 Nef occurs via SH3 disengagement while the kinase tail remains bound to the SH2 domain of Hck [44]. Thus, further studies are required to elucidate the full mechanism for W121R's ability to overcome Csk inactivation.…”
Section: Mutations Stabilizing the Open Conformation Can Prevent Downmentioning
confidence: 91%